Hypoxia alters expression of Zebrafish Microtubule-associated protein Tau (mapta, maptb) gene transcripts - Nik, M.; Newman, M.; Ganesan, S.; Chen, M.; Martins, R.; Verdile, Giuseppe; Lardelli, M. (BioMed Central, 2014)
Background: Microtubule-associated protein tau (MAPT) is abundant in neurons and functions in assembly and stabilization of microtubules to maintain cytoskeletal structure. Human MAPT transcripts undergo alternative splicing to produce 3R and 4R isoforms normally present at approximately equal levels in the adult brain. Imbalance of the 3R-4R isoform ratio can affect microtubule binding and assembly and may promote tau hyperphosphorylation and neurofibrillary tangle formation as seen in neurodegenerative diseases such as frontotemporal dementia (FTD) and Alzheimer’s disease (AD). Conditions involving hypoxia such as cerebral ischemia and stroke can promote similar tau pathology but whether hypoxic conditions cause changes in MAPT isoform formation has not been widely explored. We previously identified two paralogues (co-orthologues) of MAPT in zebrafish, mapta and maptb. Results: In this study we assess the splicing of transcripts of these genes in adult zebrafish brain under hypoxic conditions. We find hypoxia causes increases in particular mapta and maptb transcript isoforms, particularly the 6R and 4R isoforms of mapta and maptb respectively. Expression of the zebrafish orthologue of human TRA2B, tra2b, that encodes a protein binding to MAPT transcripts and regulating splicing, was reduced under hypoxic conditions, similar to observations in AD brain. Conclusion: Overall, our findings indicate that hypoxia can alter splicing of zebrafish MAPT co-orthologues promoting formation of longer transcripts and possibly generating Mapt proteins more prone to hyperphosphorylation. This supports the use of zebrafish to provide insight into the mechanisms regulating MAPT transcript splicing under conditions that promote neuronal dysfunction and degeneration.